Activation of Sigma-1 Receptor by Cutamesine Attenuates Neuronal Apoptosis by Inhibiting Endoplasmic Reticulum Stress and Mitochondrial Dysfunction in a Rat Model of Asphyxia Cardiac Arrest. Issue 1 (January 2019) - Qin, Jiahong; Wang, Peng; Li, Yi; Yao, Lan; Liu, Yuanshan; Yu, Tao; Lin, Jiali; Fang, Xiangshao; Huang, Zitong
ABSTRACT: Background: Global cerebral ischemic/reperfusion (I/R) injury after cardiac arrest (CA) is a major cause of mortality and morbidity in survivors of resuscitation. We utilized a rat model of asphyxia CA to explore the functional effects and mechanisms of Sigma-1 receptor (Sig-1R) activation in cerebral protection using the Sig-1R agonist cutamesine (SA-4503). Methods: After resuscitation, the surviving rats were randomly divided into three groups (n = 18 each): the cardiopulmonary resuscitation (CPR) group (0.9% saline at 1 mL/kg); the SA4503 low-dose group (1 mg/kg SA4503); and the SA4503 high-dose group (2.5 mg/kg SA4503). The neurological deficit scores were recorded, and the cerebral cortex was harvested for western blotting. Mitochondrial transmembrane potential, adenosine triphosphate (ATP) concentrations, calcium homeostasis, and mitochondrial ultrastructure were also studied. Results: The SA4503 treatment groups exhibited improved neurological outcomes compared with the CPR group. The protein levels of caspase-3 and the endoplasmic reticulum stress markers C/EBP homologous protein and caspase-12 were lower in the SA4503 treatment groups compared with the CPR group. SA4503 treatment also normalized mitochondrial membrane potential, tissue ATP concentrations, intracellular Ca 2+ overload, and upregulated Sig-1R protein level compared with the CPR group. The SA4503 high dose treatment showed significant cerebral protective effects compared with the SA4503 low dose treatment. The therapeutic effect of SA4503 was dose-dependent. Conclusions: CA downregulated Sig-1R protein expression. Activating Sig-1R using SA4503 protected against global cerebral I/R injury in a rat model of asphyxia CA by alleviating endoplasmic reticulum stress and mitochondrial dysfunction and eventually inhibiting neuronal apoptosis.